IMPACT OF IMPLEMENTATION OF METHODS OF COACHING FOR SUCCESS, PARTICIPATIVE, AFFILIATIVE, VISIONARY AND SITUATIONAL (COPAVISIT) AT OPERATIONAL MANAGEMENT OF CELLULAR TELECOMMUNICATIONS COMPANIES IN DIGITAL ERA - Hendra Jonathan Sibarani; Nidya Banuari; Esther Praja Anggriany Panggabean (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The development of the telecommunications industry in Indonesia is determined by the company's ability to manage operational with using methods of coaching for success, participative, affiliative, visionary and situational. The meaning of coaching for success are with treating people as they want to be treated, that is by indirectly giving punishment, participative by taking part in the problems faced by company management, affiliative by maintaining good relationships with employees and company partners, visionary support progress company, situational is done by looking at the condition of the company that is required to be able to implement the marketing industry 4.0. This research method uses a quantitative approach, the type of quantitative descriptive research with the nature of research that is explanatory. The data used are secondary data, namely employees of cellular telecommunication in Area of Regional I of Medan City as many as 800 people. The sampling technique used in this study using the Slovin formula so that the number of samples used in this study was 89 people. Sampling uses a simple random sampling approach. The results obtained in this study are coaching for success methods have a negative and significant influence, participative and affiliative, have a positive and significant influence, while visionary and situational have no influence on the operational management of cellular telecommunications companies in Medan City.